(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
Cryptocurrencies are an important current and future development. This importance has led to numerous studies, but there has been no explicit study to demonstrate their impact on accounting as a contemporary and future topic. Hence, this study explores the impact of cryptocurrencies on the objectives of financial statements. The research aims to shed light on the accounting system, its components, developments, and related concepts and components. It also aims to examine the concept of cryptocurrencies, their types, characteristics, and forms. It also aims to demonstrate the impact of cryptocurrencies on the components of the accounting system, which is the primary objective of the study. To achieve the research objectives and answer its questions, the researchers adopted the deductive-analytical approach in the theoretical aspect and the inductive approach in the practical aspect. Data and information were obtained through a questionnaire prepared by the researcher to obtain the opinions of the study sample. The study reached several conclusions, the most important of which was that cryptocurrency transactions are characterized by transparency and clarity due to the use of modern technologies such as blockchain, which reduces the likelihood of fraud, errors, and forgery. Furthermore, cryptocurrencies are issued using mathematical encryption and security technologies to secure financial transactions and transfer them safely. The study also concluded that the use of cryptocurrencies in the unified accounting system requires in-depth knowledge and understanding of the technology, laws, and regulations related to these currencies. In light of his study, the researcher recommended enhancing the knowledge of professionals and academics regarding cryptocurrencies, their uses, and the detailed aspects of the accounting system, given their close connection to practical accounting applications in the field. He also recommended the need to encourage institutions to engage experts in the field of accounting and crypto financial technologies to evaluate and develop the components of the unified accounting system to effectively and appropriately address the impact of cryptocurrencies.